G629 Evaluating a telehealth project to support parental monitoring of signs of infection in children with neuropathic bladder. (27th April 2016) - Carter, B; Whittaker, K; Dix, J; Sanders, C
Abstract : Children with neuropathic bladder are at risk from the short and long term consequences of urinary tract infections. Early identification of infection can reduce morbidity and improve the management. This longitudinal study used a concurrent mixed methods (qualitative and quantitative) research design, to evaluate a telehealth intervention that aimed to support parents to monitor their child's urine and identify clinical signs of infection. The study was theoretically underpinned by a framework of self-efficacy. The telehealth intervention was run from the children's urology service within a single paediatric tertiary referral centre. The evaluation aimed to explore stakeholders' experiences and perceptions of the telehealth intervention. The stakeholders included parents of the index children, clinicians and technical experts. The index children were all aged <5 years and had spina bifida and/or neuropathic bladder. Face-to-face and remote one-to-one interviews, surveys and group interviews were undertaken with key stakeholders at three time points. Secondary data were also utilised. Thematic analysis and structured evaluation analysis were used for the qualitative data. Simple descriptive statistics were used with the quantitative data. Findings show that remote monitoring benefited the children, the parents and the clinicians. The parents were very positive about the benefits accruing from remote monitoring; these benefits included more effective use of parental time and feeling more confident due partly to the 'hard evidence' from the print-out of results from the home urine testing. Collectively these experiences contributed to a greater sense of parental control over the daily management of their child's health which parents identified as empowering. Clinical and technical stakeholders invested considerable time into the set up of the intervention not least in navigating the specific processes for implementing paediatric telehealth. This required a shift in team resources to ensure alerts triggered by the telehealth system received timely responses and appropriate actions. Lessons learned from this intervention include the need to set alerts sufficiently sensitively and the increased workload on top of usual service provision.